(2-Methylquinolin-8-olato-kappa N-2,O)diphenyl(thiocyanato-kappa N)tin(IV) - Najafi, E.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The Sn-IV atom in the title compound, [Sn(C6H5)(2)-(C10H8NO)(NCS)], is chelated by the 2-methylquinolin-8-olate anion and is five-coordinate in a trigonal-bipramidal geometry [C-Sn-C = 133.47 (13) and 138.77 (12)degrees]. There are two independent molecules of similar conformation in the asymmetric unit.